Early down-regulation of chorismate mutase 2 gene expression in a sugarcane cultivar tolerant to Xanthomonas albilineans infection - Rosa-Santos, T. M. [UNESP]; Nogueira, L. F.; Paz, T. A. [UNESP]; Silva, R. G. da [UNESP]; Silva, J. O. L.; Creste, S.; Zingaretti, S. M. [UNESP] (Funpec-editora, 2019)
Xanthomonas albilineans causes leaf scald disease, one of the most economically important diseases of sugarcane. Leaf scald is a systemic and vascular disease that can severely reduce productivity. The best and primary method of leaf scald control is the use of tolerant cultivars. Knowing that cell wall lignification is a plant defense mechanism and that chorismate mutase is relevant in this process, we analyzed the expression pattern of the chorismate mutase 2 (SoCM2) gene in two contrasting sugarcane cultivars by RT-qPCR. A similar pattern of downregulation for the SoCM2 gene was observed in both cultivars; however, after 72h, the tolerant cultivar (RB867515) showed repression of the SoCM2 gene, while for the susceptible cultivar (SP78-4467), SoCM2 gene downregulation occurred only after 144h. Here we propose that early repression of the SoCM2 gene is responsible for tolerance to X. albilineans infection in the sugarcane cultivar RB867515.
Keywords: Biotic stress; Chorismate mutase 2; Cytosolic; Sugarcane